The factors affecting student's satisfaction in University Utara Malaysia, Kedah - Nurul Hidayah, Md Noor (2015)
Theoretically, education can be considered as one of important and fruitful investment that all the time rewards in numerous ways. The strong and effective educational systems results in the greater performance of the students. Based on Muhamd, Rizwan and Ali (2010) state “the educational institutions where the system is affective and administration is willing to provide the quality services always enjoy more incoming of brilliant and talented students.” Student paying fee tuition in higher education, they deserve to get something in high quality that suits with the value of money paying for tuition fee. The level of satisfaction among the student being as a scale in measuring whether HEI afford to deliver or provided services, technology, and facilities in effective ways. This study empirically examines the relationship between campus services, technology, and campus facilities and students’ satisfaction and which factors impact on student’s satisfaction in University Utara Malaysia, Kedah. The sample size in this study was 377 undergraduate student of UUM. The result of this study shown the positive relationship between campus services, technology, and campus facilities and students’ satisfaction, but only campus services is significant with students’ satisfaction